Através da sala escura: dinâmicas espaciais de comunicação audiovisual - aproximações entre a sala de cinema e o lugar do Vjing - Menotti, Gabriel (2007)
The subject of this research is film consumption and how it circumscribes the relation between spectator and image. What motivates our investigation is a certain delay in the cinematographic industry: even though film production has been expanded throughout history, benefiting from the new conditions of the image, the same hasn't occurred to film distribution and exhibition. In fact, these two links of the chain have become stiffer within the years, and cannot deal with all the potentials of a filmic work any longer. In the meantime, another circuit for audiovisual consumption has spinned off from the experiences of color music and light show: VJing, the screening of real-time generated, edited or composed video. Free from the constraints of an established industry, VJing is still open to the possibilities of emerging technologies. So, albeit it does not pose itself as a direct alternative to the movie theater, the VJing space (VJ arena) can give us clues about its development. The differences between both circuits become evident in the way by which their respective consumption spaces are organized as media and serve to the construction of meaning. So, in the light of the history of cinematographic screening, our work has the double objective of suggesting prototypes for a future movie theater, more coherent with the conditions of the digital movie, as well as establishing cinema as a paradigm for the study of VJing. In order to do so, we will confront classical theories of cinematographic fruition with the historical development of the screening spaces, having in mind some artistic experiences that insert themselves critically in the movie theater. That way, we aim to create an articulation between the concepts of cinema situation, mobilized virtual gaze and interface, in order to create a basis for the comparison between the conventional movie theater and the place of the VJing, as well as between the dynamics of audiovisual communication presupposed by each space